Leadership and Management Practice at MAN 2 Kulon Progo: School Principal’s Reflection - Zahro, Khamilatul; Widiyan, Agung Purwa (DAS Institute, 2024)
This study aims to critically analyze the innovative leadership and management practices at MAN 2 Kulon Progo in creating a dynamic and inclusive learning environment. Utilizing a qualitative descriptive method, data were collected through purposive interviews with key school principal and observations, alongside a review of supporting documents to provide in-depth insights. The findings indicate that MAN 2 Kulon Progo has successfully fostered a dynamic and inclusive learning environment. The principal's active involvement in daily school activities, combined with effective communication strategies, has fostered transparency and trust within the school community. These practices have ensured that all members feel valued and heard, which is crucial for building a cohesive and collaborative atmosphere. The principal's ability to motivate and inspire staff and students has significantly enhanced teacher performance and student engagement. The study underscores the importance of participatory leadership, continuous professional development, and adaptive management practices in achieving educational excellence. It offers valuable recommendations for other educational institutions seeking to improve their leadership and management approaches, emphasizing the need for principals who are both managers and inspirational leaders.